SHELLFISH AND FISH BIODIVERSITY OF MANGROVE ECOSYSTEMS IN LEIZHOU PENINSULA, CHINA - Han Wei-dong; Lui Jin-ke; He Xiu-Ling; Cai Ying-Ya; Ye Fu-liang; Xuan Li-qiang; Ye Ning (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Leizhou Peninsula is located in the south most continental tip of China with longitude 109:30110d, latitude 2012 2 35, and with a north tropical oceanic monsoon climate. Among its total inter tide area 99 100 hm2, its mangrove wetlands occupy an area of 20 279 hm2, including 7 305.8 hm2 mangrove and 9 609.7hm2 mudflats suitable for mangrove growing, and was designated as one of wetlands of international importance by the centre government of The People’s Republic of China in January 2002. The survey we carried out into the eight major mangrove areas of Leizhou Peninsula by using various nets and tools between July 14 and September 4, 2002 showed that there were 3 order 38 family 110 species of shellfish and 127 species of fish, belonging to 15 order 58 family 100 genera, living in the mangrove areas. Among them, more than 28 species of shellfish and 34 species of fish were regarded as economical species with some importance of economy respectively. The structures of shellfish and fish resource were discussed, and the authors proposed that the conservation efforts should be secured for future sustainable development of the mangrove biodiversity resources in Leizhou Peninsula.